Thalassaemia Prevention: Bangladesh Perspective - A Current Update (Bangladesh Journal of Child Health, 2017)
Thalassaemias are a group of autosomal recessive disorder and the most common inherited disease worldwide with a wide geographical variation in incidence. Bangladesh, a developing country, having a population over 160 million. World Health Organization (WHO) has estimated that 3% of our population carries ?- thalassaemia and 4% of population carries Hb-E in Bangladesh. But recently Khan WA showed that carrier status of Hb-E is 6.1% and as high as 41.7% in tribal school children in Bangladesh. Since Thalassaemia is a severe and incurable disease, it is only manageable when it is prevented. The WHO has advocated and promoted the programs for thalassaemia prevention from the early 1970s. Several countries have already set up comprehensive national thalassaemia prevention programs but in our country most of the population is unware of this hereditary disease. The rapidly growing number of children diagnosed as thalassaemia in Bangladesh clearly indicate that thalassaemia will be a emerging health burden for our country. So, we need to prevent thalassaemia before its too late by comprehensive national integrated prevention programs which include public awareness and education, carrier screening, genetic counseling, premarital screening and prenatal diagnosis. Thalassaemia prevention program has become a community concern as it affects marriage practices and reproduction. So, ethical issues need to be addressed for proper implementation of this by government policy, central control and co-ordination according to the local structures, social values, religious laws and cultural tradition of our country.Bangladesh J Child Health 2016; VOL 40 (1) :31-38